PENDEKATAN LEAN HOSPITAL UNTUK MENGIDENTIFIKASI WASTE KRITIS PELAYANAN OBAT DI INSTALASI FARMASI RAWAT JALAN RSUD X MANNA TAHUN 2020 - Dinda Sri Rahayu; Titik Sunarni; Opstaria Saptarini (MEDIA ILMU KESEHATAN, 2020)
Background: Lean Hospital is needed in order to hospital can fulfill patient’s needs optimally, can give health service as much as possible to the patient. This research has a purpose for identifying medicine service, waste and the root cause of waste, so than we give reparation suggestion to medicine service that happens in Outpatient Pharmacy Installation of Regional Public Hospital. Objective: Respondent In this study, patients or their families and pharmacy Methods: This research is study case research with qualitative approach. The research stages are doing observation of service process’s flow which is made in value stream mapping, distributing questionnaires of patient’s value and waste, doing interview by 5 why method for knowing the root cause and waste critical. The proposed of improvements is obtained from Head of Hospital Pharmacy Installation. Results: The research result showed that the service medicine process of pharmacy installation has been lean. Waste critical that is obtained, is waste motion 21,1%. Conclusion: The root cause of waste motion is manually, there is a space that separates between rooms, Emergency Installation/ IGD’s service, Outpatient and Inpatient has not been done separately yet. Adding visual management, rearranging the layout of the room is a suggestion for improvements to eliminate waste.